Microbiological analysis of red meat, poultry and eggs - Mead, G. C. (Woodhead Publishing in food science, technology and nutrition, 2007)
Microbiological analysis is an established tool in controlling the safety and quality of foods. This work discusses the key aspects of microbiological analysis, such as sampling methods, use of fecal indicators, current approached to testing of foods, detection and enumeration of pathogens and microbial identification techniques